2017
DOI: 10.4158/ep161634.ra
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Learning and Clinical Practice Improvement for Diabetes in the Hospital: A Review of Educational Interventions for Providers

Abstract: Objective The management of inpatient hyperglycemia and diabetes requires expertise among many healthcare providers. There is limited evidence about how education for healthcare providers can result in optimization of clinical outcomes. The purpose of this critical review of the literature is to examine methods and outcomes related to educational interventions regarding the management of diabetes and dysglycemia in the hospital setting. This report provides recommendations to advance learning, curricular plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Recent calls have been made for IGC education to reach a larger population of learners and be adopted as a formal component of hospitals' quality planning, aiming to integrate clinical practice guidelines and optimize inpatient diabetes care (36). The Centers for Medicare and Medicaid Services recently contracted with Health Services Advisory Group to provide services for the Medication Measures Special Innovation Project, which is designed to develop measures that can be used to support quality healthcare delivery (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent calls have been made for IGC education to reach a larger population of learners and be adopted as a formal component of hospitals' quality planning, aiming to integrate clinical practice guidelines and optimize inpatient diabetes care (36). The Centers for Medicare and Medicaid Services recently contracted with Health Services Advisory Group to provide services for the Medication Measures Special Innovation Project, which is designed to develop measures that can be used to support quality healthcare delivery (37).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of 16 educational programs in this area, 14 studies reported at least 1 clinical process or outcome measure, whereas 7 reported glycemic outcomes. 11 Among the 7 studies reporting glycemic outcomes, 3 showed reductions in rates of hyperglycemia with a concomitant increase in rates of hypoglycemia, 12,31,32 3 showed a reduction in rates of hyperglycemia with no change in rates of hypoglycemia, 13,33,34 and 1 study showed no effect on either hyperglycemia or hypoglycemia. 14 The educational formats in these studies included daily endocrine rounds with endocrine faculty, lectures/workshops, personal digital assistant (PDA), print algorithms, interactive discussions applying practice recommendations, games, case-based diabetes ward rounds, and refresher courses.…”
Section: Discussionmentioning
confidence: 99%
“…Educational formats that have been developed in this area include lectures, written guidelines or algorithms, clinical decision support tools, workshops, computer-based modules, online interactive tutorials, case-based ward rounds, refresher courses, and interactive assessments. 11 Most of these studies have demonstrated effectiveness in increasing provider knowledge of inpatient glucose management and improving process measures (eg, adherence to clinical practice guidelines regarding the use of basal-bolus insulin therapy) 4 ; on the other hand, results have been mixed regarding the effectiveness of educational interventions on glycemic outcomes. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perspectives of inpatient providers ratified a need of clinicians, and endorsed the development of the CDS tool and its implementation program. 32 Prior to the integration of the tool in the clinical EMR environment, we conducted an exhaustive authentication process. This consisted in direct chart audits for accuracy verification of algorithmic workflows enabling cases detection.…”
Section: Methodsmentioning
confidence: 99%